Patient and healthcare professional perspectives on implementing patient-reported outcome measures in gender-affirming care: a qualitative study - Melissa Stepney; Abhilash Jain; Jeremy Rodrigues; Rakhshan Kamran; Liam Jackman; Anna Laws; Conrad Harrison (BMJ Open Quality, 2023)
Objectives Patient and healthcare professional perspectives are needed to develop a gender-affirming care patient-reported outcome measure (PROM) implementation plan. We aimed to identify top considerations relevant to gender-affirming care PROM implementation from patient and healthcare professional perspectives.Design, settings and participants This qualitative study conducted in the UK between January and April 2023 includes focus groups with a patient sample diverse in age and gender identity, and a healthcare professional sample diverse in age and role. Established methods in implementation science and the Consolidated Framework for Implementation Research were used to create interview guides, and analyse data. Focus groups were audio recorded, transcribed verbatim and analysed by two independent researchers. Patient and healthcare professional focus groups were conducted separately.Primary outcome measures Patient and healthcare professional perspectives on PROM implementation were explored through focus groups and until data saturation.Results A total of 7 virtual focus groups were conducted with 24 participants (14 patients, mean (SD) age, 43 (14.5); 10 healthcare professionals, mean (SD) age, 46 (11.3)). From patient perspectives, key barriers to PROM implementation were mistrust with PROMs, lack of accessibility, burden, and lack of communication on why PROMs are important and how they will help care. From healthcare professional perspectives, key barriers to PROM implementation were lack of accessibility, burden with PROM administration and scoring, costs of implementation (financial and time), and lack of communication on what PROMs are and how they benefit service provision.Conclusion Gender-affirming care PROM implementation must address: patient mistrust with PROMs, accessibility, communication on what PROMs are and how they can be used, reducing burden, and hybridised implementation. These factors may also be applicable to other clinical areas interested in implementing PROMs.